Eternity and a day [videorecording (DVD)] = Mia aiōniotēta kai mia mera - Angelopoulos, Thodōros, 1935-2012; Ganz, Bruno; Renauld, Isabelle; Bentivoglio, Fabrizio, 1957-; Skevis, Achilleas; Arvanitis, Giorgos (New Yorker Video, 2006)
A famous writer is told he has only a few days to live. He meets a young boy on the street, an illegal immigrant from Albania, and decides to take him back home. During the trip, the writer hopes to learn about life and death.